Goat milk soap from expired powdered milk/ Rosliza Ali ... [et al.] - Ali, Rosliza; Zulkifli, Norsakina Zurina; Salleh, Nunshaimah; Fadzil, Adibatul Husna; Yaacob, Yanti; Mohmad Tahirudin, Nordiana Suhada (2023)
This study aims to formulate the goat milk soap using expired powdered milk and study the effectiveness of the soap. The expired powdered milk was weighed, dissolved with distilled water and frozen prior to use. The frozen milk was mixed with caustic lye. The combination of coconut oil, olive oil and franch oil in variable amounts was prepared and added to the milk-lye mixture. The mixture solution was carefully stirred with a hand mixer until the batter became thicker. Few drops of fragrance oil was added to enhance the aroma. The findings indicate that F3 had better hardness, scent, and solubility properties than other soap formulations.